2018
DOI: 10.1093/cid/ciy267
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Antiretroviral Regimens on Cerebrospinal Fluid Viral Escape in a Prospective Multicohort Study of Antiretroviral Therapy-Experienced Human Immunodeficiency Virus-1–Infected Adults in the United States

Abstract: Protease inhibitors were independent predictors of cerebrospinal fluid (CSF) escape in antiretroviral therapy (ART)–experienced human immunodeficiency virus–infected adults. M184V/I combined with thymidine analog mutations were more frequent in adults with CSF escape compared to no escape. These findings suggest optimizing ART may reduce likelihood of CSF escape.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
73
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(89 citation statements)
references
References 40 publications
15
73
1
Order By: Relevance
“…Multiple studies have shown poor central nervous system penetration and sub-therapeutic concentrations achieved within the CNS with Atazanavir (Peluso et al, 2012;Lahiri et al, 2016). While longitudinal studies have evaluated the relationship between viral escape and multiple cART regimens, the clinical syndrome of viral escape in the CNS associated with PIs have not been clearly characterized so far (Best et al, 2009;Mukerji et al, 2018). In this study we describe the clinical syndrome, laboratory profile, radiological features and outcomes of eleven patients on PI based regimens with features consistent with symptomatic central nervous system (CNS) viral escape from a tertiary care institution from South India.…”
mentioning
confidence: 99%
“…Multiple studies have shown poor central nervous system penetration and sub-therapeutic concentrations achieved within the CNS with Atazanavir (Peluso et al, 2012;Lahiri et al, 2016). While longitudinal studies have evaluated the relationship between viral escape and multiple cART regimens, the clinical syndrome of viral escape in the CNS associated with PIs have not been clearly characterized so far (Best et al, 2009;Mukerji et al, 2018). In this study we describe the clinical syndrome, laboratory profile, radiological features and outcomes of eleven patients on PI based regimens with features consistent with symptomatic central nervous system (CNS) viral escape from a tertiary care institution from South India.…”
mentioning
confidence: 99%
“…Even in the era of cART, HIV replication and low-level expression of HIV proteins in the brain and periphery and the ensuing inflammatory response are likely to underlie many of the neuronal complications associated with HIV-infection (Ko et al, 2018;Levine et al, 2016;Tso et al, 2018). While cART has reduced viral load in the periphery, instances of distinct virus isolated from CSF (viral escape) and antibodies against HIV proteins found in the brain provide evidence of low-level viral replication and HIV protein expression in brains of patients on ART (Ferretti et al, 2015;Levine et al, 2016;Mukerji et al, 2018). While high levels of HIV replication in the brain are not detectable in the cART era, antibodies for HIV proteins and HIV genomic DNA have been found in CSF and in brains of HIV + decedents that were on cART (Bachani, Sacktor, McArthur, Nath, & Rumbaugh, 2013;Ko et al, 2018;Tso et al, 2018).…”
Section: Hiv Proteins and Mitochondrial Dysfunction In The Cnsmentioning
confidence: 99%
“…The metabolic responses include alterations in ROS, ATP production, lactate production, oxygen consumption and autophagic flux. These metabolic changes precede, or are concomitant with, induction of inflammatory gene expression (Lee et al, 2018;Natarajaseenivasan et al, 2018;Van den Bossche et al, 2017). This is consistent with a growing body of evidence indicating that increased activation of glial cells compromises the bioenergetic substrate pool available to neurons and thereby limits neuronal bioenergetic capacity ( Jiang & Cadenas, 2014;Yin et al, 2016).…”
Section: Hiv Proteins and Immunometabolismmentioning
confidence: 99%
See 2 more Smart Citations